Where People Live and Die Makes a Difference: Individual and Geographic Disparities in Well-Being Progression at the End of Life - Denis Gerstorf; Nilam Ram; Jan Goebel; Jürgen Schupp; Ulman Lindenberger; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Lifespan psychological research has long been interested in the contextual embeddedness of individual development. To examine if and how regional factors relate to between-person disparities in the progression of late-life well-being, we applied three-level growth curve models to 24-year longitudinal data from deceased participants of the German Socio-Economic Panel Study (N = 3,427; age at death: 18 to 101 years). Results indicate steep declines in well-being with impending death, with some 8% of the between-person differences in both level and decline of well-being reflecting between-county differences. Exploratory analyses revealed that individuals living and dying in less affluent counties reported lower late-life well-being, controlling for key individual predictors including age at death, gender, education, and household income. The regional factors examined did not directly relate to well-being change, but were found to moderate (e.g., amplify) the disparities in change attributed to individual factors. Our results suggest that resource-poor counties provide relatively less fertile grounds for successful aging until the end of life and may serve to exacerbate disparities. We conclude that examinations of how individual and residential characteristics interact can further our understanding of individual psychological outcomes and suggest routes for future inquiry.
Keywords: I12; J14; R23; 330; Neighborhoods; Selective mortality; successful aging; differential aging; psychosocial factors; well-being; longitudinal methods; Alternde Bevölkerung; Soziale Lage; Alterskrankheit; Sterblichkeit; Gerontologie; Humangeographie